2019
DOI: 10.3389/fpsyt.2019.00852
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress Mediates the Relationship of Body Image and Depressive Symptoms in Individuals With Obesity

Abstract: Obesity is a world-wide increasing condition classified by a BMI ≥ 30 kg/m2 that is frequently accompanied by various somatic comorbidities as well as an increased risk for mental comorbidities. Studies show associations of obesity with symptoms of depression, lower quality of life, and higher (perceived) stress compared to the general population. Body image has also been shown to play an important role in eating and weight disorders. The present study therefore aims to contribute to the understanding of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…Ultra-processed food consumption increases the risk of excessive weight gain and obesity. People with obesity are more frequently dissatisfied with their bodies compared to those with a normal weight, affecting perceived stress [35]. Additionally, a study has shown a positive association between perceived stress and the combination of high unhealthy food consumption, such as junk food, and a negative association with healthy foods, such as fruits and vegetables [36].…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-processed food consumption increases the risk of excessive weight gain and obesity. People with obesity are more frequently dissatisfied with their bodies compared to those with a normal weight, affecting perceived stress [35]. Additionally, a study has shown a positive association between perceived stress and the combination of high unhealthy food consumption, such as junk food, and a negative association with healthy foods, such as fruits and vegetables [36].…”
Section: Discussionmentioning
confidence: 99%
“…So far, a common interpretation of associations between disordered eating, body image, and depression was that obese people have “healthy” body dissatisfaction due to their excess weight that normalizes when they adopt healthy eating habits and normalize their weight. Instead, our study along with other literature [ 8 , 9 , 20 , 21 ] suggests that a subgroup of patients with obesity presents with pathological body image in the sense of body dissatisfaction, overvaluation of weight and shape, and low self-esteem. It is known that these symptoms can even deteriorate after bariatric surgery, since most patients suffer from excess skin [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that overall psychosocial functioning improves after bariatric surgery [4,7], yet the likelihood of improvement and its mechanism remain unclear. A relevant mechanism of psychosocial functioning in obesity might be the interactions between disordered eating, depression and body image [4,8,9]. The latter is a fundamental aspect of the self-concept, because it is a constant characteristic and includes meaning of the body for self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…This measure has been applied in numerous studies and clinical settings, showing satisfactory psychometric properties and especially a high sensitivity to change and detect eating disorders, e.g., anorexia nervosa (Löwe and Clement, 1996;Albani et al, 2006a;Mölbert et al, 2018). It was also applied to specify body dysmorphia disorder (Sack et al, 2002;Schieber and Martin, 2016) and measure the effects of different group therapy interventions in patients with multiple sclerosis (Tesar et al, 2003;Veleva et al, 2018), cancer (Grübel, 2003;Esser et al, 2018), a heart attack (Löwe et al, 2002) and obesity (Hotter et al, 2003;Ziser et al, 2019). Besides that, it was revealed that patients with a mental illness or pronounced psychological distress reported higher values on the RBI subscale and lower values on the VBD subscale (Löwe et al, 2003).…”
Section: Introductionmentioning
confidence: 99%